TECHNOLOGY ACCEPTED MODEL PADA PENGGUNAAN TEKNOLOGIDALAM PROSES PEMBELAJARAN AKUNTANSI - Erna Pasanda; Andi Kusuma; Kartini (Paulus Journal of Accounting (PJA), 2020)
TECHNOLOGY ACCEPTED MODEL IN THE USE OFTECHNOLOGY IN THE ACCOUNTING LEARNING PROCESS.This study aims to find out the meaning of one of the accountingolympiad students regarding the acceptance of technology in theaccounting learning process. The research setting is in the AccountingOlympiad activities throughout Makassar city and surrounding areas.This research is a post-positivism research with interpretive paradigmand transcendental phenomenology research methodology. Thephenomenologist chose one Olympic participant as the informant. Theanalysis technique uses Noema, Epoche, Noesis, Intentional Analysisand Eidetic Reduction. The meaning of technology acceptance inaccounting learning according to these students is that technology canbe accepted in the learning process of accounting (Usage behavior)when it has been practiced, which can lead to the desire (Intention toUse) to use the technology (Perceived Usefulness) especially if thetechnology is easy to use ( Perceived Ease of Use).